2014
DOI: 10.1177/1541931214581437
|View full text |Cite
|
Sign up to set email alerts
|

Designing Unambiguous Auditory Crash Warning Systems

Abstract: A series of three studies examined the acoustic characteristics that contribute to a sound being unambiguously perceived as an urgent alarm within a vehicle context. In experiment 1, participants sorted a variety of sounds modeled after sounds currently in use in driver-vehicle interfaces (DVIs) into categories indicating highly critical warnings and alerts (or "alarms"), vehicle status sounds, or in vehicle social notifications. Results indicated that four criteria (peak-to-total time ratio, interburst interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…Although this research observed substantial differences among auditory signals, it did not systematically manipulate acoustic parameters and features to develop specific recommended design criteria. Lewis et al (2014) provide a model for such systematic consideration of critical signal parameters. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this research observed substantial differences among auditory signals, it did not systematically manipulate acoustic parameters and features to develop specific recommended design criteria. Lewis et al (2014) provide a model for such systematic consideration of critical signal parameters. …”
Section: Discussionmentioning
confidence: 99%
“…There is opportunity for confusion when a signal is unfamiliar or is used in a manner different from the listener's past experience. Researchers have been addressing the features of auditory signals that lead to appropriate categorical perception (i.e, the sound naturally conveys the appropriate general category of meaning to a naive listener; Lewis, Eisert, Roberts, & Baldwin, 2014). Such research may provide features or parameter boundaries that result in a given signal conveying the intended general message.…”
Section: Objectivesmentioning
confidence: 99%
“…Sorting methods have the advantage of lending themselves to analysis of the contribution of individual parameters to overall categorization by use of regression analyses. For example, Lewis et al (2014) found that the auditory parameters of peak to total time ratio, interburst interval, number of harmonics and base frequency explained around 61% of the variance in alarm categorization for a large set of in-vehicle information system sounds. In sum, sorting methods provide an efficient means of categorizing large numbers of stimuli and provide an effective way to examine how stimulus parameters independently and interactively impact signal perception.…”
Section: Discussionmentioning
confidence: 99%
“…Sorting is a particularly efficient method of categorizing stimuli when there are a large number of stimuli to be evaluated (Bonebright, Miner, Goldsmith, & Caudell, 2005) above and beyond more traditional paired comparison methods (Bonebright, 1996). Sorting methods can also determine which acoustic components make a sound seem like an "Alarm" or a "Social Notification" (Lewis, Eisert, Roberts, & Baldwin, 2014). The goal of the present study was to compare magnitude estimation methods of psychophysical scaling with sorting methods in order to determine the correlation between perceived urgency and signal categorization in an in-vehicle context.…”
Section: Introductionmentioning
confidence: 99%
“…HMI can be considered as the channel through which information are conveyed to a vehicle's occupant; HMI design is one of the main issues that must be properly allowed for [5], addressing, for instance, the definition of the correct stimulus (type: visual, acoustic, haptic, etc. ; sequence; timing; priority; etc.).…”
Section: Present Advanced Driver Assistance Systemsmentioning
confidence: 99%